The crustal architecture of Myanmar imaged through zircon U-Pb, Lu-Hf and O isotopes: Tectonic and metallogenic implications - Nicholas J. Gardiner (2018)
© 2018 International Association for Gondwana Research The Tethys margin in central and eastern Asia is comprised of continental terranes separated by suture zones, some of which remain cryptic. Determining the crustal architecture, and therefore the geological history, of the Eastern Tethyan margin remains challenging. Sited in the heart of this region, Myanmar is a highly prospective but poorly explored minerals jurisdiction. A better understanding of Myanmar's mineralization can only be realized through a better understanding of its tectonic history, itself reflected in at least four major magmatic belts. The Eastern and the Main Range Provinces are associated with the Late Permian to Early Triassic closure of Palaeo-Tethys. The Mogok–Mandalay–Mergui Belt and Wuntho–Popa Arc are a response to the Eocene closure of Neo-Tethys. However, magmatic ages outside these two orogenic events are also recorded. We present new zircon U-Pb, Lu-Hf and O isotope data from magmatic rocks across Myanmar, which we append to the existing dataset to isotopically characterize Myanmar's magmatic belts. Eastern Province Permian I-type magmatism has evolved εHf (−10.9 to −6.4), whilst Main Range Province Triassic S-type magmatism also records evolved εHf (−13.5 to −8.8). The Mogok-Mandalay-Mergui Belt is here divided into the Tin Province and the Mogok Metamorphic Belt. The Tin Province hosts ca. 77–50 Ma magmatism with evolved εHf (−1.2 to −15.2), and δ18O of 5.6–8.3‰. The Mogok Metamorphic Belt exhibits a more complex magmatic and metamorphic history, and granitoids record Jurassic, Late Cretaceous, and Eocene to Miocene phases of magmatism, all of which exhibit evolved εHf values between −4.6 and −17.6, and δ18O between 6.3 and 9.2‰. From the Tagaung-Myitkyina Belt, we report a magmatic age of 172 Ma and εHf of 18.1 to 10.8. To accommodate the geological evidence, we propose a tectonic model for Myanmar involving a greater Sibumasu – where the documented zircon isotopic variations reflect compositional variations in magmatic source – and invoke the role of a Tengchong Block. The Baoshan Block and Greater Sibumasu were likely assembled on or before the Triassic, a former Andean margin and suture which may lie across the Northern Shan Plateau, and reflected in isotopic differences between the northern and southern parts of the Mogok Metamorphic Belt. This contiguous Sibumasu–Baoshan Block then sutured onto the Indochina margin in the Late Triassic. We propose that a Tengchong Block within Myanmar provides for a southerly termination of the Meso-Tethys suture immediately north of the Mogok area. A discrete Tengchong Block may explain a discontinuous arc of Late Triassic to Jurassic I-type magmatism in central Myanmar, representing an Andean-type margin sited above a subducting Meso-Tethys on the margin of Sibumasu. The Tengchong Block sutured onto Greater Sibumasu before the Late Cretaceous, after which subduction of Neo-Tethys drove the magmatism of the Wuntho-Popa Arc and ultimately that of the Tin Province. The metallogenic character of granite belts in Myanmar reflects the crustal architecture of the region, which is remarkable for its prolific endowment of granite-hosted Sn-W mineralization in two quite distinct granite belts related to sequential Indosinian and Himalayan orogenesis.